Knockdown of GRHL3 Inhibits Activities and Induces Cell Cycle Arrest and Apoptosis of Human Colorectal Cancer Cells - 王小康;周芬芳;陶浩冉;王昕;张弛;苏飞;王诗培;徐利华;潘雪凯;冯茂辉;谢伟 (Current medical science, 2017)
The Grainyhead-like 3（GRHL3） is involved in epidermal barrier formation, neural tube closure and wound repair. Previous studies have suggested that GRHL3 has been linked to many different types of cancers. However, to date, its effects on human colorectal cancer（CRC） has not been clarified yet. Our microarray analysis has indicated predominant GRHL3 expression in CRC. The purpose of this study was to investigate the expression and significance of GRHL3 in CRC tumorigenesis using CRC tissues and paired paracancerous tissues, as well as using distinct CRC cell lines（HT29 and DLD1）. We observed increased GRHL3 expression at both m RNA and protein levels in CRC tissues and CRC cell lines using quantitative real-time polymerase chain reaction（q RT-PCR） and Western blotting. Moreover, silencing GRHL3 with si RNA could suppress CRC cell proliferation, viability and migration in vitro. We also found that knockdown of GRHL3 could promote cell cycle arrest at G0/G1 phase in HT29 cells and DLD1 cells, and induce cell apoptosis in HT29 cells. Together, our study revealed the down-regulation of GRHL3 in vitro could inhibit CRC cell activity and trigger cell cycle arrest at G0/G1 phase and apoptosis.